Consumer Perception Towards Fresh Meat and Processed Meat Consump tion in the City of Tirupati, India (Indian Journal of Animal Production and Management, 2026)
A study was conducted to understand consumer perception towards meat  and meat products consumption in Tirupati city. The city of Tirupati has  witnessed a sharp rise in households, which is evident from the rapid  expansion of the city outskirts by means of real-estate developments. This  poses a greater scope for meat startups to be established in the rapidly  developing city. A total of 200 respondents were randomly selected and  interviewed. Data were collected using a pre-tested structured interview  schedule through personal interviews. The study group comprised 76 males  and 124 females. The educational background of respondents was found to  vary between uneducated and PG & PhD levels. The overall mean age of the  consumers was found to be 33.5, of which the majority (45%) belong to the  middle age group. The study revealed that most of the consumers ate meat  for taste (67%) and health benefits (33%) and usually consume meat twice a  week (51%). The most preferred meat was chicken (53%), followed by chevon  (21%), seafood (fish, prawns) at 16%, and other meat at 10%. Gravy-type  meat products were most preferred, followed by biryani (19%) and fried meat  products (15%). Most of the consumers (63%) opined that meat has good  cholesterol (HDL) and (28%) as bad cholesterol (LDL), whereas (9%) opined  as both. The willingness to purchase chilled/frozen meat was very low (5%).  The acceptance of the respondents towards processed meat products such as  pickles was 80%, and comminuted meat products were at 20%, respectively.  The majority of the respondents (82%) believed that overconsumption of  meat leads to heart problems and other diseases. Unfortunately, (78%) of  the respondents have no idea about what kind of vitamins and minerals are  present in meat. Most of the consumers said that the ideal methods for cooking  are boiling (78%) and frying (22%). Only (40%) of the respondents have  awareness about zoonotic diseases. Food safety has emerged as an important  global issue with international trade and public health implications. The  current study also revealed that most of the respondents have no idea about  laws pertaining to food safety. The results indicated that most respondents  consume meat for taste and as a cultural tradition. However,  the majority of the consumers lack a scientific backdrop  about fresh meat and processed meat, which can further be  overcome by conducting extensive awareness programs and  advertisements by government agencies and entrepreneurs  in the meat trade. Consumer awareness about the scientific  handling of meat can safeguard their health and also pave  the way for huge investments in meat startups in developing  cities.
Keywords: Consumer, consumption pattern, meat, food safety.